New records and AMS radiocarbon dates on Quaternary Walrus ( Odobenus Rosmarus ) from New Brunswick - Miller, Randall (Géographie physique et Quaternaire, 1997)
AbstractWalrus fossils are occasionally recovered during scallop dragging in the Bay of Fundy and from sand and gravel deposits along the coastline of New Brunswick in eastern Canada. Six new fossils and four new AMS radiocarbon dates significantly increase the information concerning late-glacial to postglacial walrus in New Brunswick. Dates range from about 12 800 BP to 2 900 BP, almost half falling between 9 000 and 10 000 BP. Temporal distribution of walrus, compared to estimates of past summer sea surface temperature, suggest that in the Bay of Fundy walrus occurred in waters ranging from 12 to 15° C.